2021
DOI: 10.21744/lingcure.v5ns2.1663
|View full text |Cite
|
Sign up to set email alerts
|

contrastive study of grammar translation method and direct method in teaching of English language to primary school pupils

Abstract: There have always been different methods of teaching and learning of English language and throughout the years these methods have changed and improved. The Grammar Translation Method is one of the first and the main methods in teaching and learning of English language. This method enables the learning through the translation of various texts and the study of grammatical rules, which is its main activity. Moreover, in a class where Grammar Translation Method is used the target language is used less while the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This method ensures that the students acquire fluency in the target language by focusing on skills such as listening, speaking, writing, etc. (Spahiu & Kryeziu, 2021). Just as its name suggests, this method serves as a direct link between the speaker and the language itself, as a student shouldn't rely on his native language while using this method.…”
Section: Literature Review 21 Grammar-translation Methods and Direct ...mentioning
confidence: 99%
“…This method ensures that the students acquire fluency in the target language by focusing on skills such as listening, speaking, writing, etc. (Spahiu & Kryeziu, 2021). Just as its name suggests, this method serves as a direct link between the speaker and the language itself, as a student shouldn't rely on his native language while using this method.…”
Section: Literature Review 21 Grammar-translation Methods and Direct ...mentioning
confidence: 99%
“…As for the method of grammar translation, we have the method of teaching and learning of the English language which allows respecting the textual and normative characteristics of the language. Thus, it is considered the most effective method used by students (Spahiu and Kryeziu, 2021;Ricra 2019). On the other side, there is also the direct method which proposes translation using actions and demonstrations of what is to be learned.…”
Section: Developmentmentioning
confidence: 99%
“…In addition, the students reported that GMT is less of speaking performance and correction the incorrect speaking. Recent research by Spahui and Kryeziu (2021) has made great strides toward GTM in online classroom which was less effective in preparing the students to use their target language communicatively. Eisa (2020) made a strong case on the GTM which was unable to build communicative interaction between the students and the teacher in EFL classroom.…”
Section: Questionmentioning
confidence: 99%